A random change point model for cognitive decline in Alzheimer’s disease and mild cognitive impairment - Yu, Lei (2012)
BACKGROUND: We present a random change point model to characterize decline in cognition among community-based elderly who developed Alzheimer’s disease (AD) or amnestic mild cognitive impairment (MCI), and to examine how decline varies with age, sex, education, and APOE status. METHODS: Using longitudinal cohort data on cognitive function, we fit a piecewise linear trajectory with a random change point that allows different rates of cognitive decline before and after the change point. We estimated the change point that signals the onset of cognitive impairment, and examined the association of risk factors with the location of the change point as well as the rates of decline before and after the change point. RESULTS: Among participants who were dementia free at enrollment and developed incident AD, the change point occurred on average 5.7 years after enrollment and the rate of cognitive decline after the change point nearly quadrupled. Age, education, and APOE status play important but different roles in the timing of the onset of cognitive impairment and in the rates of decline before and after its onset. Results were similar among participants who were cognitively unimpaired at enrollment but later developed amnestic MCI or AD. CONCLUSIONS: The random change point model provides a more comprehensive understanding of the relation of risk factors with the onset of cognitive impairment and rates of decline before and after its onset.